Boundary spanning and knowledge exploration in a professional services firm. Issue 3 (12th October 2018) - Louise Mors, Marie; Rogan, Michelle; Lynch, Susan E
ABSTRACT: Exploration for new knowledge is critical to the performance of professional service firms. The networks of partners in professional service firms are thought to be important for knowledge exploration because they typically span both the firm's internal and external boundaries aiding the flow of novel information to the firm. Yet, to date prior studies of individual-level boundary spanning have focused primarily on the benefits of boundary spanning and only recently begun to address the costs of building and maintaining boundary spanning ties. We add to this stream of research and propose that the knowledge exploration benefits of internal boundary spanning ties accrue more slowly than the costs, resulting in a curvilinear relationship with knowledge exploration. Moreover, we propose that the effects of internal and external boundary spanning ties on exploration are interdependent, because effective exploration requires not only the selection of ideas externally, but also their transmission internally. Our study of 1, 449 ties of partners in a consulting firm supports these arguments providing a more nuanced view of boundary spanning ties for knowledge exploration in professional service firms.